Gambaran Kualitas Hidup Pasien Diabetes Melitus Menggunakan Instrumen DQLCTQ Studi Kasus : Puskesmas X Kota Pontianak - Yuda Pratama K; Muhammad Akib Yuswar; Fajar Nugraha (Indonesian Journal of Pharmaceutical Education, 2023)
Diabetes Mellitus (DM) is a metabolic disease characterized by chronic hyperglycemia and abnormalities in carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action or both. In Indonesia, the prevalence of DM is around 4.8%, for the Pontianak City area, DM is included in the top 10 diseases that dominate throughout 2019, which ranges from 12,913 cases. The purpose of this study was to describe the quality of life and characteristics of DM patients using the DQLCTQ. This research is a prospective study, using the Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ) questionnaire which consists of several questions that will be filled in by patients suffering from DM at the X Health Center, Pontianak City. The results showed that the quality of life of DM patients at X Health Center was still low, namely 50.98% of patients. This result is due to various factors such as gender, age, education, marital status and occupation. The conclusion from this study is that some DM sufferers at the X Health Center, Pontianak City are still lacking in implementing a healthy lifestyle so that the value of their quality of life is still low.